(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the difficulties that arise when using only traditional methods to teach foreign languages. It discusses the limitations of traditional approaches such as grammar-translation and audiolingual methods and highlights the need for more interactive and modern teaching strategies. The study examines challenges faced by both teachers and students and suggests ways to overcome these obstacles for more effective language learning. This study revealed several key challenges associated with using only traditional methods in teaching foreign languages. The data from surveys, interviews, and classroom observations provided a clear picture of these challenges from both teachers’ and students’ perspectives. The challenges of using only traditional methods in teaching foreign languages are clear. These methods can lead to disengaged students, an imbalance in language skills, and difficulties in practical application. Additionally, teachers need more support to incorporate a variety of teaching techniques. By combining traditional methods with more interactive and communicative approaches, educators can create a more effective and engaging language learning experience. This balanced approach can help students not only learn the language but also use it confidently in real-world situations.